Factors Affecting the Extent of Agricultural Land Conversion on the Household Economy of Rice Farmers - Rezza Hardanovita; Nuriah Yuliati; Gyska Indah Harya (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Agricultural land conversion not only threatens the sustainability of the farm sector, but also influences the socioeconomic conditions of farmer. The purpose of this study is to examine the external and internal factors affecting agricultural land conversion on the household economy of rice farmers. Using a quantitative survey approach, this study collected primary data from 30 rice farmers in Kloposepuluh Village, Sidoarjo Regency, selected through purposive sampling. Secondary data were obtained from official sources, including government agencies and regional planning documents. The influence of independent variables on land conversion was examined using multiple linear regression analysis. Results show some variables significantly influence on land conversion, including land area ownership, influences from developers and other farmers, employment opportunities, and economic pressures. These variables encourage farmers to convert their land to non-farm uses. On the other hand, land conversion is not significantly affected by government policy variables, indicating the weak effectiveness of policy interventions in controlling land conversion. The results highlight the need for the government to play an active role in enhancing agricultural land protection policies by adopting more adaptive and participatory strategies. Furthermore, providing economic incentives and safeguarding farmers is expected to reduce the economic pressures that lead to land conversion.